PENGARUH IOT TERHADAP PENINGKATAN PENJUALAN BERBASIS SYARIAH TERHADAP PRODUK KERUK IKAN GURIH CAP IKAN TENGGIRI - Nadila Amanda (Jurnal Al Wadiah, 2023)
The Internet of Things (IoT) has become a rapidly growing technology trend in recent years. IoT enables connectivity between physical devices and digital systems, which can be used for various purposes, including increasing sales. In this study, we investigated the impact of IoT on increasing sharia-based sales of the Cap Ikan Tenggiri savory fish cracker product. This study used a quantitative method with a survey approach. Data were collected through questionnaires distributed to customers of the Cap Ikan Tenggiri savory fish cracker product. The results of the study showed that IoT has a positive impact on increasing sharia-based sales of the Cap Ikan Tenggiri savory fish cracker product. IoT can increase sharia-based sales through several ways, namely: (1) Increase customer transparency and trust: IoT can provide customers with more transparent information about the product, production process, and delivery. This can increase customer trust and encourage them to buy the product. (2) Increase marketing efficiency and effectiveness: IoT can be used to target customers more accurately and effectively. This can increase marketing efficiency and effectiveness, which can lead to increased sales. (3) Increase customer satisfaction: IoT can be used to collect customer feedback in real time. This feedback can be used to improve product and service quality, which can increase customer satisfaction. Based on the results of this study, it is recommended that the Cap Ikan Tenggiri savory fish cracker company can utilize IoT to increase sharia-based sales. The company can implement IoT solutions to improve customer transparency and trust, marketing efficiency and effectiveness, and customer satisfaction.